2007
DOI: 10.1161/circulationaha.106.679951
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Reduction of Ischemic Mitral Regurgitation by Papillary Muscle Repositioning

Abstract: Background-Recurrent ischemic mitral regurgitation (IMR) is frequent despite initial reduction by annuloplasty becausecontinued LV remodeling increases tethering to the infarcted papillary muscle (PM). We have previously shown that PM repositioning by an external patch device can acutely reduce IMR. In this study, we tested the hypothesis that IMR reduction persists despite possible continued LV remodeling. Methods and Results-In 7 sheep, we used a chronic ischemic posterior infarct model that produces LV dila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
1
28
0
1
Order By: Relevance
“…Referring to measured values of HRV variables in patients with an implanted artificial valve, excellent patient survival rate was found in the followup period on average of almost 3 years (some patients were followed-up with in a period of 6 years). Reading recent texts on cardiac valve surgery operation techniques [13][14][15][16] and speaking with experienced cardiac surgeons about possible reasons for the obtained differences in the results of this study between groups of patients with an implanted artificial aortic vs. mitral valve, we found that in principle, as long as there are no complications, surgical implantation of an artificial aortic valve lasts shorter than surgical implantation of an artificial mitral valve. Referring to that, the heart arrest, or duration of cardioplegia and hypothermia are shorter during aortic valve surgery than during mitral valve surgery, that certainly can partly explained the obtained differences in results of this study [17,18].…”
Section: Discussionmentioning
confidence: 65%
“…Referring to measured values of HRV variables in patients with an implanted artificial valve, excellent patient survival rate was found in the followup period on average of almost 3 years (some patients were followed-up with in a period of 6 years). Reading recent texts on cardiac valve surgery operation techniques [13][14][15][16] and speaking with experienced cardiac surgeons about possible reasons for the obtained differences in the results of this study between groups of patients with an implanted artificial aortic vs. mitral valve, we found that in principle, as long as there are no complications, surgical implantation of an artificial aortic valve lasts shorter than surgical implantation of an artificial mitral valve. Referring to that, the heart arrest, or duration of cardioplegia and hypothermia are shorter during aortic valve surgery than during mitral valve surgery, that certainly can partly explained the obtained differences in results of this study [17,18].…”
Section: Discussionmentioning
confidence: 65%
“…Decreases in MR after CRT have been attributed to a complex interaction of mechanisms, including recoordination of the papillary muscle closing forces, 20,23,24 reductions in LV volumes with decreases in mitral leaflet tenting angles, and augmentation of transmitral pressure gradient attributable to increased contractility. 22,25,26 Breithardt et al showed that reduction in MR immediately after CRT was directly related to the increase in (r=−0.83; P<0.0001).…”
Section: Mechanisms Of Improvement In Mr After Crtmentioning
confidence: 99%
“…Attempts to restore a normal anatomic relationship of the papillary muscles may therefore result in less tethering of the leafl ets and a potential for more durable elimination of ischemic regurgitation. Recently, such potential was re-demonstrated experimentally in a sheep model by Hung et al [21]. Using a patch balloon device sewn epicardially at the region of induced infarction, they were able to incrementally reduce the degree of papillary muscle displacement, thereby eliminating tethering, with a reduction in regurgitation that persisted up to 8 weeks after the procedure [21].…”
Section: Papillary Muscle Relocation Techniquesmentioning
confidence: 98%
“…Recently, such potential was re-demonstrated experimentally in a sheep model by Hung et al [21]. Using a patch balloon device sewn epicardially at the region of induced infarction, they were able to incrementally reduce the degree of papillary muscle displacement, thereby eliminating tethering, with a reduction in regurgitation that persisted up to 8 weeks after the procedure [21]. This epicardial approach has yet to be applied in humans.…”
Section: Papillary Muscle Relocation Techniquesmentioning
confidence: 99%